Pregnancy outcomes among evacuees of the Sinabung volcano, 2010–2018 (North Sumatra, Indonesia): A matched cohort study. Issue 2 (17th June 2021) - Kushnick, Geoff; Behie, Alison; Zuska, Fikarwin
Abstract: Objectives: Exposure to natural disasters during pregnancy is associated with adverse birth outcomes and increased probability of female births. Nonetheless, relatively little work has been done on evacuations of women living in close vicinity to volcanic eruptions. We conducted a retrospective cohort study among women from villages near the Sinabung volcano in North Sumatra, Indonesia, which has been active since 2010. Methods: We compared an "exposed" sample of women ( n  = 97) who were pregnant when forced to evacuate their villages due to the volcanic eruptions and an "unexposed" sample of non‐evacuees ( n  = 97) matched for age and year of child's birth. We collected anthropometric data (height and weight of each woman) and conducted structured interviews about pregnancy outcomes and evacuation‐related stress. Results: Evacuation led to an almost five‐fold increase in the adjusted odds of having an early or preterm birth in non‐imputed (OR = 4.84, 95% CI: 1.31–17.92) and multiply imputed (OR = 4.84, 95% CI: 1.29–19.19) analyses. It also led to approximately a 1 cm decrease in birth length in the non‐imputed ( β  = −1.10, 95% CI: −1.96–0.24) and multiply imputed ( β  = −1.17, 95% CI: −1.20–0.36) analyses, both including controls for confounders. We found decreasing birth length with increasing stress among evacuees. There was no discernible effect of evacuation or stress on the other outcomes. Conclusions: Both adverse effects we documented can exert negative influences on later‐in‐life outcomes for children of women pregnant during evacuation. This should be considered when developing protocols for supporting women and connecting them with clinical resources when evacuated from natural disasters.